Urban sustainability in Old City Centres, a Comparison Between the City of Najaf in Iraq and Italian Cities Experiences - Sabeeh Lafta Farhan; Ihsan Abbass Jasim; Ahmed Naji (Engineering and Technology Journal, 2016)
This paper discusses the current situationinold cities ofIraq, whichis not commensuratewiththe highprestige andsanctity ofwhatit containsandwhatit represents of rarityandtypicality. The aim of the research is tobuild a baseof knowledge about the urbansustainabilityin development ofthe historiccity centers and in particular city of Najaf,the center ofNajaf. The research also explores the possibilities of benefiting from theItalian citiesexperiences to reach a state ofconsistencyand harmonybetween the variousplanningdimensions, tokeep thefunctional, structural and spatialsustainabilityandcultural heritage, and tocreatea sustainable environmentfor theoccupants, visitors and workers. Theoretical part of the paper includes definitions for methods of dealing with historic cities then displays the treaties and conventions, which are important as they represent the gist of schematic scientific thought on the global level, Iraq is committed to (such as Athens Conference, the Hague Act 1954, Gobineau Conference in 1960, UNESCO 1962, UNESCO in 1962, the Kyoto criteria in 1967, the Paris meeting in 1968, the Rome Conference in 1972, the Rome Declaration in 1983, etc.) Then, second part studying Italian cities experiences of the historic centers, for example (Florence, Venice, Bologna), It is important to have a precise analysis according to the approved urban sustainability criteria. In the third part, the paper presents the condition of the old city of Najaf through the available information and field work, which included obtaining information on the structural, demographic, economic, administrative, religious, cultural and environmental aspects and the infrastructure in the old city of Najaf to diagnose the strengths and weaknesses. After comparing with the Italian cities experiences, the paper proposes plans for the restructuring of the old city of Najaf Ashraf and then recommendations.